PENGARUH POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN EMOSI ANAK USIA 3-4 TAHUN DI KB. AR- RAUDHOH LARANGAN DALAM KECAMATAN LARANGAN KABUPATEN PAMEKASAN TAHUN PELAJARAN 2021-2022 - Shadrissaid Shadrissaid; Wahono Wahono; Naili Sa’ida (Universitas Muhammadiyah Surabaya, 2022)
The purpose of this study was to determine the effect of parenting styles on the emotional development of children aged 3-4 years in Kb. Ar- Raudhoh Prohibition in Prohibition Subdistrict, Pamekasan Regency for the 2021- 2022 Academic Year. Parenting patterns can be part of a child's emotional development. The research method used in this research is quantitative. With data collection techniques by observation, interviews, documentation. Data analysis used descriptively such as data reduction, data display, data verification. Then the validity of the data is carried out with the Triangulation technique. The results obtained in this study are that parenting influences the emotional development of children aged 3-4 years in KB AR Raudhoh Larangan Dalam Kec. District Ban. Pamekasan Academic Year 2021/2022. This is evidenced by the calculated chi- square value of8.231. Thus the null hypothesis was rejected and the working hypothesis was accepted, while the contingency coefficient analysis obtained KK = 0.464.Â Keywords: parenting; parents; hypothesis